STRATEGI PERANCANGAN KAWASAN PERUMAHAN BERKELANJUTAN DENGAN PENDEKATAN WATER SENSITIVE URBAN DESIGN DI KAWASAN BANDUNG UTARA - Putri, Tika Novis; Asriana, Nova; Farhabi, Yoska (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2021)
Abstract: The rapid growth of settlement in the northern part of Bandung, as well as known KBU, increases slightly as an impact of the economy growth in the capital city of West Java. These influences strongly has some effects, such as the changing of land use and the decreasing of water absorption. For instance, the agricultural land area, the conservation area and the green area become settlement area and commercial area, therefore this area is a lack of absorption area due to the declining the green area. These evidences are following checked according to the WALHIâ€™s data, around 70% of green area, such as protected forest, agricultural land, and plantation area leads to be settlement area, residential area and commercial area. Mostly Bandung Raya, included Cimahi, South Bandung, and Kabupaten Bandung get flood as the effect of these issues, especially when rain season. Based on the issues explanation and evidences, this research aims to have problem solving in the development of environmental friendly settlement and residential area that will lead to sustainable residences and conservation area. This research purpose is to conduct experimental-based and explorative-based the development model of sustainable residences in the Kelurahan Citeureup, one of sub-district in the North Bandung, through Water Sensitive Urban Design (WSUD) approach. This approach is not only study from architectural aspect, but also study from landscape and the utilities aspects. Meanwhile, this method of this study is to conduct morphology analysis to recognize the pattern and urban structure, also the water flow patterns in this area. The result then will be used to elaborate the strategic developing for environmental friendly settlement and residential area (sustainable residences, especially in water well-disposed so that to reduce the flood impact when rain season, the shortage rainfall when dry season, and to fulfill further the sustainability of water needs.Abstrak: Pertumbuhan pemukiman di Kawasan Bandung Utara (KBU) terus meningkat seiring dengan meningkatnya pertumbuhan ekonomi Kota Bandung sebagai Ibu Kota Jawa Barat. Dampak dari pertumbuhan ini adalah terjadinya alih fungsi lahan, yang sebelumnya merupakan lahan pertanian dan perkebunan, menjadi kawasan pemukiman. Sebagai Kawasan yang diandalkan menjadi daerah resapan air, kondisi KBU saat ini cukup mengkhawatirkan. Berdasarkan data yang dihimpun oleh WALHI, sekitar 70% lahan hijau yang berupa hutan lindung, lahan pertanian dan perkebunan telah beralih fungsi menjadi kawasan permukiman dan komersial. Dampaknya, dapat dilihat saat musim penghujan, dimana banjir terjadi hampir di sebagian wilayah Bandung Raya, mencakup Wilayah Cimahi, Bandung Selatan, Kabupaten Bandung, dan sekitarnya. Berdasarkan isu tersebut, diperlukan solusi terkait model pengembangan kawasan perumahan ramah lingkungan (perumahan berkelanjutan) yang mampu berperan sebagai kawasan konservasi air, selain sebagai tempat bermukim.Melalui pendekatan Water Sensitive Urban Design (WSUD), penelitian ini mencoba mengeksplorasi model pengembangan perumahan berkelanjutan di Kelurahan Citeureup, salah satu kelurahan di Kawasan Bandung Utara,Â tidak hanya dari segi arsitektur bangunan, namun juga terkait lansekap dan utilitas kawasan. Metode yang dilakukan dalam penelitian ini adalah dengan melakukan analisis morfologi kawasan untuk memahami pola dan struktur ruang kawasan dan pola pergerakan aliran air. Hasil dari analisis tersebut selanjutnya digunakan untuk merumuskan strategi pengembangan kawasan perumahan yang ramah lingkungan (perumahan berkelanjutan) khususnya dalam hal ini ramah air, sehingga dapat turut mengurangi dampak banjir ketika musim penghujan, kekeringan di musim kemarau, serta untuk memenuhi kebutuhan air berkelanjutan di masa depan.